Scaffold Hopping from Amodiaquine to Novel Nurr1 Agonist Chemotypes via Microscale Analogue Libraries. (21st February 2022) - Willems, Sabine; Müller, Marcel; Ohrndorf, Julia; Heering, Jan; Proschak, Ewgenij; Merk, Daniel
Abstract: Several lines of evidence suggest the ligand‐sensing transcription factor Nurr1 as a promising target to treat neurodegenerative diseases. Nurr1 modulators to validate and exploit this therapeutic potential are rare, however. To identify novel Nurr1 agonist chemotypes, we have employed the Nurr1 activator amodiaquine as template for microscale analogue library synthesis. The first set of analogues was based on the 7‐chloroquiolin‐4‐amine core fragment of amodiaquine and revealed superior N‐substituents compared to diethylaminomethylphenol contained in the template. A second library of analogues was subsequently prepared to replace the chloroquinolineamine scaffold. The two sets of analogues enabled a full scaffold hop from amodiaquine to a novel Nurr1 agonist sharing no structural features with the lead but comprising superior potency on Nurr1. Additionally, pharmacophore modeling based on the entire set of active and inactive analogues suggested key features for Nurr1 agonists. Abstract : The nuclear receptor Nurr1 is considered a neuroprotective transcription factor and ascribed high therapeutic potential, but Nurr1 activators are rare. Using the Nurr1 agonist amodiaquine as starting point, microscale analogue libraries were synthesized and tested in a cellular setting to identify new Nurr1 ligand scaffolds. Thereby, novel synthetic Nurr1 activators exceeding amodiaquine in potency were obtained.